DOMESTICATION OF TRIPLETAIL FISH (Lobotes surinamensis) FROM BATAM SEAWATER AND IT’S GROWTH IN NETCAGE - Sahidan Muhlis; Hendrianto Hendrianto; Salsal Purba; Agung Darmono; Kurniawan Kurniawan (Universitas Riau Kepulauan, 2018)
Kakap Lobo fish (Lobotes surinamensis) still belong to wildlife fish with economical price. Kakap Lobo known as tripletail fish, black barramundi and leaf fish. So far there is no report in Indonesia about successful of Kakap Lobo farm or cultured. Cause of that, BPBL Batam try to domesticate Lobo as the alternative fish that potential to culture and give the more economical price. The objective of this activity is to domesticate the captured Lobo then culture sea net cage. Domesticated done seven months in Dec 2016 till Juli 2017 in sea floating net cage. Lobo seeds found on the surface around net-cage put into the pompano cultured net, the size almost same, and cultured together. Lobo seeds initial size 1,0 – 6,9 gram (average 3,5 gram) in bodyweight amount 21 fishes fed same as pompano feed pellets. The cultured result as long as seven months gain the final body weight of Lobo 1.091,0 – 1.381,5 (average 1,175,0 gram), average daily growth 5,58 gram/day and survival rate 100%. BPBL Batam succeeds domesticate Lobo fish and cultured in sea net cage.